1997
DOI: 10.1097/00005373-199705000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Pressure and Bone Marrow Fat Intravasation in Unreamed Femoral Nailing

Abstract: Intramedullary pressure increased significantly in the reamed more than in the unreamed group. Bone marrow fat intravasation depended on the rise in intramedullary pressure, and occurred less frequently in unreamed than in reamed intramedullary femoral fracture stabilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 31 publications
2
30
0
2
Order By: Relevance
“…Although the employment of unreamed medullary nailing reduced the increase in intramedullary pressure and the intravazation of bone marrow components, 12 experiments showed an increase in pressure above the physiological level accompanied by a clinical relevant intravasation of bone marrow components. 13 The reason for this is the stamp effect that leads to an increase in pressure when the nail is inserted.…”
Section: Discussionmentioning
confidence: 94%
“…Although the employment of unreamed medullary nailing reduced the increase in intramedullary pressure and the intravazation of bone marrow components, 12 experiments showed an increase in pressure above the physiological level accompanied by a clinical relevant intravasation of bone marrow components. 13 The reason for this is the stamp effect that leads to an increase in pressure when the nail is inserted.…”
Section: Discussionmentioning
confidence: 94%
“…The unreamed technique uses a smaller device with theoretical advantages re- garding all these risks. Kropfl et al (1997) reported that bone marrow intravasation occurred less frequently in unreamed than in reamed intramedullary femoral fracture stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between intramedullary pressure and FE has led to the development of specific strategies in trauma surgery [90]. External fixation or fixation with a plate produces less lung injury than intramedullary fixation [66].…”
Section: Surgical Strategies For Preventing Fesmentioning
confidence: 99%